ASSOCIATION OF TUMOUR NECROSIS FACTOR-ALPHA -308 G/A PROMOTER POLYMORPHISM WITH SUSCEPTIBILITY AND DISEASE PROFILE OF RHEUMATOID ARTHRITIS - khurshid, Sadia; Zeb, Alam; Bano, Saira; Rasheed, Uzma; Zammurrad, Shazia; Khan, Muhammad Sufyan; Khursheed, Tayyaba; Aziz, Wajahat (Journal of Ayub Medical College Abbottabad, 2020)
Background: Single nucleotide polymorphism underlying the auto-immune process governing the pathologic manifestations of rheumatoid arthritis has been the focus of study for quite a while. TNF-alpha -308 G/A promoter polymorphism has been reported to be responsible for a number of manifestations of rheumatoid arthritis. methods: This case-control study was conducted at the department of Rheumatology at Pakistan Institute of Medical Sciences Islamabad from 9th May to 9th August 2019 with a focus to determine the Association of tumour necrosis factor-alpha -308 G/A promoter polymorphism with susceptibility and disease profile of rheumatoid arthritis. One hundred and fifty cases with diagnosed rheumatoid arthritis and 150 age and gender matched controls were enrolled in the study. Their genotyping was done for tumour necrosis factor-alpha -308 G/A promoter polymorphism. Results: The genotypic analysis showed that GG genotype was the most common genotype found in 118 cases (78.66%) followed by GA (18.66%) and AA genotype (2.6%) p=0.0096 in both cases and controls. Overall, G allele was more common than A in both cases and controls pointing towards the preponderance of G genotype in our population. (p=0.003). However, the GA genotype and A allelotype was more common among cases with rheumatoid arthritis (p <0.05). No significant association of G/A polymorphism with smoking and gender, however, within gender, males had a significantly more expression of the GA genotype and A allelotype (p <0.05). Conclusion: There is a significantly more expression of the GA genotype and the A allelotype of the TNF-alpha -308 G/A promoter gene in rheumatoid arthritis patients in our population. Similarly, more males, compared to females have increased expression of the GA genotype as well as the A allelotype. Keywords: Rheumatoid Arthritis; Tumour necrosis factor alpha; Auto-immune disease; Single nucleotide polymorphism; Allelotype